The Ostarbeiter of Graffenstaden - Sumpf, Alexandre (Sensus Historiae, 2025)
Today, in the Strasbourg suburb of Illkirch-Graffenstaden, nothing suggests that there was once one of the largest civilian internment camps of the wartime era. Between autumn 1942 and the very beginning of 1945, hundreds of ‘Ostarbeiter’ lived there, destined for the German war effort. Between volunteering and deportation, economic exploitation and racist violence, agentivity and local humanitarianism, their presence draw a different map of Alsace, de facto annexed to the Third Reich.